Implementation of Waste Management Policy in Karawang Regency - Eden Komarudin Soeardi (Sean Institute, 2023)
Changes in both human behavior and the patterns of human life can be attributed to very rapid population expansion. This also has an affect on the environment around it, which may either be positive or harmful, depending on the circumstances. One region that struggles with effectively managing its waste is the Karawang Regency. The purpose of this study is to assess the degree to which waste management policies in Karawang regency have been put into practice and to determine the degree to which these policies have been successful. A case study is the type of research that is carried out, which include conducting interviews with relevant parties and making field observations. The findings of the research indicate that the policy on waste management in Karawang Regency has been implemented well; however, there are still some challenges that need to be conquered in order to increase the efficacy of the policy.